Ozone and cause-specific cardiorespiratory morbidity and mortality. Issue 9 (23rd October 2009) - Halonen, Jaana I; Lanki, Timo; Tiittanen, Pekka; Niemi, Jarkko V; Loh, Miranda; Pekkanen, Juha
Abstract : Background: Health effects of ozone have been observed in numerous studies. However, analyses of more cause-specific morbidity or mortality outcomes have rarely been performed. A study was undertaken to determine the short-term associations of ozone with cause-specific cardiorespiratory mortality and morbidity by age groups. Methods: Daily levels of ozone were measured at a background measurement station in 1998–2004 in Helsinki, Finland. All analyses were a priori restricted to the warm season. Daily cause-specific cardiorespiratory mortality and hospital admissions were studied in elderly people (≥65 years) and adults (15–64 years) and associations between ozone and asthma emergency room visits in children (<15 years) were analysed. All models were adjusted for PM2.5 and Poisson regression was used for the analyses. Results: There was a positive association between ozone and admissions for asthma-chronic obstructive pulmonary disease (COPD) in elderly people (9.6%; 95% CI 2.0% to 17.8% at 0-day lag for 25 μg/m 3 increase in ozone). Consistent associations were also found between ozone and asthma emergency room visits in children (12.6%; 95% CI 0.8% to 25.1%, 0-day lag). There was a suggestion of an association between ozone and admissions for arrhythmia among elderly people (6.4%; 95% CI 0.63% to 12.5%, 1-day lag), which was slightly confounded by PM2.5 . Conclusions: Positive associations were found for ambient ozone with asthma visits among children and with pooled asthma/COPD admissions among elderly people. The evidence for a positive association between ozone and cardiovascular health was weaker.